Karakterisasi Struktural dan Pemeringkatan Jenis Kayu untuk Penerapan Teknik di Kenya. - Mutayi, Christine O.; Sabuni, Bernadette; Waweru, Samuel; Mwasame, Geoffrey (Jurnal Teknik Sipil, 2024)
An investigation was carried out in Kakamega County to determine the characteristic grade of eucalyptus and cypress timber species that are commonly used in construction. The physical and mechanical properties of two timber species for structural use; eucalyptus and cypress were determined. Six logs of each species were obtained from different areas of Kakamega County, sliced into 2” by 12” size before seasoning under a shade and their structural strength properties were determined at a moisture content of 12%. These logs were cut into test samples for the determination of their strength properties. A total of 800 samples (100 samples for each test) free from visible defects were used for each species. Basic physical properties of the samples like moisture content and density were determined. Tensile strength, compressive strength parallel the grain, compressive strength perpendicular to the grain, and bending strength were the mechanical strength tests carried out according to Eurocode 5 (1995) and BS 5268 (2002) specifications on Universal Testing Machine (UTM). Results were analyzed statistically using Statistical Package for Social Sciences (SPSS) while grading was done according to Eurocode 5 (EC5). Cypress was graded into strength class C20 while eucalyptus was graded into strength class D24. Strength class C20 is used in load-bearing structures that require high strength, such as roof trusses and floor systems. D24 is a common structural grade for a variety of structures exposed to high environmental conditions.